Evaluation of the iron-coating technology for direct-seeded rice in the Philippines - Cañete, Sandro D.; Collado, Wilfredo B.; Sashi, Kazumichi (2022)
Field and screenhouse experiments were conducted to evaluate the performances of iron-coated (Fe-coated) seeds in wet direct-seeded rice (DSR). Effects of iron-coating on seed germination and seedling establishment, yield performance, and the fate of added iron in rice and lowland soil were measured. The germination test disclosed that the mean maximum germination rates were almost similar between the coated and uncoated seeds across varieties, whereas the iron-coated seeds took a longer time to achieve the rates.